2014
DOI: 10.5194/amt-7-3139-2014
|View full text |Cite
|
Sign up to set email alerts
|

Reconstruction of global solar radiation time series from 1933 to 2013 at the Izaña Atmospheric Observatory

Abstract: Abstract. This paper presents the reconstruction of the 80-year time series of daily global solar radiation (GSR) at the subtropical high-mountain Izaña Atmospheric Observatory (IZO) located in Tenerife (The Canary Islands, Spain). For this purpose, we combine GSR estimates from sunshine duration (SD) data using the Ångström-Prescott method over the 1933/1991 period, and GSR observations directly performed by pyranometers between 1992 and 2013. Since GSR measurements have been used as a reference, a strict qua… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
39
0
4

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 32 publications
(46 citation statements)
references
References 55 publications
3
39
0
4
Order By: Relevance
“…In the last decades, numerous analyses have demonstrated that SSR records have not been constant over time, but have undergone climatologically significant decadal variations (e.g. Pallé and Butler, 2001;Stanhill and Cohen, 2001;Sanchez-Lorenzo et al, 2007;Wild, 2009;García et al, 2014a). From the 1930s to the early 1950s the few data available suggest an increase of the SSR in the first part of the 20th century, known as early brightening.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…In the last decades, numerous analyses have demonstrated that SSR records have not been constant over time, but have undergone climatologically significant decadal variations (e.g. Pallé and Butler, 2001;Stanhill and Cohen, 2001;Sanchez-Lorenzo et al, 2007;Wild, 2009;García et al, 2014a). From the 1930s to the early 1950s the few data available suggest an increase of the SSR in the first part of the 20th century, known as early brightening.…”
Section: Introductionmentioning
confidence: 99%
“…Firstly, AOD estimations were conducted using the measured values for all parameters described in the previous section, obtaining the non-perturbed values (AOD). Secondly, the same sample was simulated again by applying the typical uncertainties of the inputs parameters reported in the literature, ±5 % for FCS (García et al, 2014a) and ±2 % for RH (Thies, 2011). For the horizontal visibility we have assumed a very conservative error of ±25 %.…”
Section: Atmosmentioning
confidence: 99%
See 2 more Smart Citations
“…The SD has been widely used by applying the wellknown Ångström-Prescott equation (Angstrom, 1924(Angstrom, , 1956Prescott, 1940) to estimate GSR H . Several authors, such as Almorox et al (2005), Yorukoglu and Celik (2006) and García et al (2014b), have used this method in different regions, obtaining similar results. The Robitzsch bimetallic pyranometer (also know as pyranograph or actnigraph, hereafter PYR), designed in the early 1920s (Robitzsch, 1926) and widely used until the late 1960s, measures GSR H from an equation involving the recorded area and the ambient temperature (Robitzsch, 1932).…”
Section: Introductionmentioning
confidence: 62%